Factors Influencing the Outcome of Symptomatic Intracranial Artery Stenosis With Hemodynamic Impairment After Short and Long-Term Stent Placement - Gong, Wentao; Zhang, Xianjun; Meng, Zhen; Liu, Feifei; Li, Guangwen; Xiao, Juan; Liu, Peng; Sun, Yujie; Liu, Tonghui; Wang, Hongxia; Zhang, Yong; Wang, Naidong (Frontiers in Neurology, 2022)
Objective Stent placement is a feasible approach worldwidely for patients with symptomatic intracranial artery stenosis (sICAS) and hemodynamic impairment (HI) who are at high risk of recurrent stroke after medical treatment. Exploration of factors associated with poor outcomes after stent placement could help develop better individualized therapeutic strategies. Methods This study conducted a post-hoc analysis of a prospective, multicenter registry study of stent use for sICAS with HI in China. Patient and clinical demographics, and stenotic lesion images were analyzed using univariate and multivariate Cox regression to the time until any endpoints or the end of the follow-up period. The short-term endpoint included any transient ischemic attack (TIA), stroke, or death within 1 month after stent placement. The long-term endpoints included the short-term endpoints and any TIA or stroke in the region of the affected artery that occurred more than 1 month after stent placement. Results Two hundred and ninety two patients were included, with 13 short-term and 39 long-term endpoints. Multivariate Cox regression analysis revealed that lesions at the arterial origin or bifurcation (Hazard Ratio (HR) = 7.52; 95% CI, 1.89–29.82; p = 0.004) were significantly associated with higher short-term risk. Baseline renal insufficiency reduced the risk (HR = 0.08; 95% CI: 0.01–0.68; p = 0.021). Factors significantly associated with higher long-term risk included irregular or ulcerated plaques at the lesion (HR = 2.15; 95% CI: 1.07–4.33; p = 0.031). Subgroup analyses indicated that higher risk occurred in the older age group (age>59 years, HR = 3.73, 95% CI: 1.27–10.97, p = 0.017), and not in the younger group (age≤59 years, HR = 1.12, 95% CI: 0.42–3.03, p = 0.822). Conclusion Irregular or ulcerated plaques in older patients and lesions at the arterial opening or bifurcation were more likely to result in adverse endpoints for stent placement during long or short -term follow-up. Investigation of these factors might facilitate the development of individualized therapeutic strategies for this population. Clinical Trial Registration http://www.clinicaltrials.gov, identifier: NCT01968122.